2002
DOI: 10.1074/jbc.m201286200
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the Ethylene Receptor ETR1 to the Endoplasmic Reticulum of Arabidopsis

Abstract: The ethylene receptor ETR1 of Arabidopsis contains transmembrane domains responsible for ethylene binding and membrane localization. Sequence analysis does not provide information as to which membrane system of the plant cell ETR1 is localized. Examination by aqueous two-phase partitioning, sucrose density-gradient centrifugation, and immunoelectron microscopy indicates that ETR1 is predominantly localized to the endoplasmic reticulum. Localization of ETR1 showed no change following a cycloheximide chase. Ethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
207
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(217 citation statements)
references
References 50 publications
5
207
0
5
Order By: Relevance
“…In plants, ethylene is perceived by a family of receptor molecules located in the endoplasmic reticulum (ER) (Chen et al, 2002). These receptor molecules share strong homology with bacterial two-component regulators (Chang et al, 1993), and are by default functionally active and are switched to an off-state by ethylene binding to the N-terminal transmembrane part of the dimerized molecule.…”
Section: Ethylenementioning
confidence: 99%
“…In plants, ethylene is perceived by a family of receptor molecules located in the endoplasmic reticulum (ER) (Chen et al, 2002). These receptor molecules share strong homology with bacterial two-component regulators (Chang et al, 1993), and are by default functionally active and are switched to an off-state by ethylene binding to the N-terminal transmembrane part of the dimerized molecule.…”
Section: Ethylenementioning
confidence: 99%
“…Immnunoblot assays were performed as described (Guo and Ecker 2003) with minor modifications. Membrane proteins were extracted according to Chen et al (2002); protein samples were mixed with 23 SDS-PAGE sample buffer, heated for 3 min at 90°C, and cooled on ice for 2 min. The proteins were fractionated by 4%-12% gradient Bis-Tris Novex precast gels (Invitrogen), transferred onto nitrocellulose filter and the blot was probed with anti-EIN2 or anti-H + -ATPase antibody (kindly provided by Dr M.J. Chrispeels).…”
Section: Antibody Preparation Immunoblot Assays and Pull-downmentioning
confidence: 99%
“…Through these screens, many ethylene mutants have been obtained, including the ethylene-insensitive mutants etr1, ein2, ein3, ein5 (Bleecker et al 1988;Guzman and Ecker 1990;Roman et al 1995); the ethylene-overproducing mutants eto1, eto2, eto3, and the ethylene constitutive response mutant ctr1 (Guzman and Ecker 1990;Kieber et al 1993). Initial studies of these mutants have revealed a mostly linear framework for the ethylene-signaling pathway, leading from ethylene perception at the membrane to transcriptional activation in the nucleus (Stepanova and Ecker 2000;Chen et al 2002;Guo and Ecker 2004).…”
mentioning
confidence: 99%
“…In Arabidopsis, ethylene is perceived by a family of five receptors that share homology to bacterial twocomponent His kinase receptors that are localized to the endoplasmic reticulum (ER) and Golgi membranes and form multimeric complexes thought to be composed of homoreceptor and heteroreceptor dimers (Chang et al, 1993;Hua et al, 1995Sakai et al, 1998;Chen et al, 2002Dong et al, 2008;Gao et al, 2008). Loss-of-function analyses indicate that the receptors act in a semiredundant manner to negatively regulate ethylene responses, although the ETR1 receptor appears to play more of a significant role in mediating ethylene responses than the other Arabidopsis receptors Cancel and Larsen, 2002;Hall and Bleecker, 2003;Wang et al, 2003;Binder et al, 2006;Qu et al, 2007).…”
mentioning
confidence: 99%